Recent changes in disclosure regulation: Description and evidence - Bethel, Jennifer E. (Journal of Corporate Finance, 2007)
Technology has dramatically reduced the cost of disclosing information to investors and created new conduits for securities' sales. The result is stock ownership, both direct and indirect, has never been more widely distributed. Equally important, changes have occurred in the institutional market for new offerings. Bought deals, Internet road shows, the preeminence of mutual funds and pension funds, and foreign investors and issuers have changed the market. In the wake of these changes, the SEC's disclosure policy has evolved. The evidence suggests we have moved from a world where information was released relatively infrequently and with significant lags to a world where information is released relatively rapidly on a continuous basis to as many investors as possible.